“In This Wound of Life …”: Dystopias and Dystopian Tropes in Chenjerai Hove’s Red Hills of Home - Mutekwa, Anias (Taylor & Francis (Routledge), 2016)
This article is a reading of Chenjerai Hove’s poetry volume Red Hills of Home (1985) as a dystopia. It locates this text within the context of the evolving postcolonial realities of the first decade of Zimbabwe’s independence. It argues that the text is informed by a dystopian import and sensibility in which forlornness, hopelessness, angst, bewilderment, pain, and betrayal mark the lived experiences of the mainly subaltern subjects who people its world which is fragmented and framed by larger forces beyond their control. It further argues that Hove mainly employs the figure of a dystopian family, together with the technique of defamiliarisation, to represent not only an existential dystopia, but also a dystopian postcolonial society, and an equally dystopian civilisation. So, it is through dystopia that Hove is able to fashion out a metalanguage with which to critique various aspects of human life and existence, Zimbabwe’s postcolonial conditions, and capitalist modernity. Because of Hove’s nativist sensibilities, the Bantu philosophy of ubuntu, and Acholonu’s motherism theory are employed to explore the ontological and gendered dimensions of the dystopian perspectives in this poetry volume.